Serious games in military applications - Samčović, Andreja B. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Serious games as one of the most important trends in e-learning are presented in this paper. An intensive use of information and communication technologies has led to major changes in traditional military education. One of these changes is the use of serious games for simulating the real military environment. This review paper presents several definitions and classifications of serious games, the difference between serious and entertainment games, and considers their military applications in training and simulation systems as well as in education.
Keywords: serious games; video games; military education; simulation